Marketing w sporcie na przykładzie polskiej piłki siatkowej mężczyzn = Marketing in sport on the example of the Polish volleyball team - Matuszak, Emilia; Muszkieta, Radosław; Napierała, Marek; Cieślicka, Mirosława; Zukow, Walery; Karaskova, Vlastimila; Iermakov, Sergii; Bartik, Pavol; Ziółkowski, Andrzej (Journal of Education, Health and Sport, 2015)
Matuszak Emilia, Muszkieta Radosław, Napierała Marek, Cieślicka Mirosława, Zukow Walery, Karaskova Vlastimila, Iermakov Sergii, Bartik Pavol, Ziółkowski Andrzej. Marketing w sporcie na przykładzie polskiej piłki siatkowej mężczyzn = Marketing in sport on the example of the Polish volleyball team. Journal of Education, Health and Sport. 2015;5(5):312-334. ISSN 2391-8306. DOI 10.5281/zenodo.17797 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A312-334 https://pbn.nauka.gov.pl/works/561046 http://dx.doi.org/10.5281/zenodo.17797 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. Marketing w sporcie na przykładzie polskiej piłki siatkowej mężczyzn Marketing in sport on the example of the Polish volleyball team Emilia Matuszak, Radosław Muszkieta, Marek Napierała, Mirosława Cieślicka, Walery Zukow, Vlastimila Karaskova, Sergii Iermakov, Pavol Bartik, Andrzej Ziółkowski Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: marketing, sport, piłka siatkowa, produkt, cena, promocja, dystrybucja, sponsoring, reklama. Keywords: marketing, sports, volleyball, product, price, promotion, distribution, sponsorship, advertising. Streszczenie Praca skupia się na marketingu w sporcie na przykładzie polskiej piłki siatkowej. Celem badań było określenie wiedzy na temat marketingu w polskiej piłce siatkowej, w jaki sposób oraz w jakim stopniu stosowany jest marketing. Badania zostały przeprowadzone internetowo przy pomocy kwestionariusza ankiety. Ankietowanymi były osoby korzystające z Internetu oraz interesujące się piłką siatkową. Wyniki wskazały, że cały czas rozwija się marketing w polskiej siatkówce oraz, że wiedza badanych na temat marketingu w piłce siatkowej jest duża. Ankietowani wiedzą jak powinna wyglądać promocja oraz w jaki sposób można lepiej promować piłkę siatkową w naszym kraju. Abstract Work focuses on marketing in sports on the example of the Polish volleyball. Aim of the study was to determine the knowledge of Polish volleyball marketing, how and to what extent is used for marketing. Tests have been carried out online with the help of a questionnaire survey. Survey on persons using the Internet and interesting like ball volleyball. The results indicated that all the time developing marketing in the retina and that knowledge test on marketing for men's volleyball is large. It know how should look like promotion and how you can better promote volleyball in our country.